2015
DOI: 10.1016/j.psychres.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotional memory in pregnant women at risk for postpartum depression

Abstract: Postpartum depression (PPD) is a serious disorder associated with debilitating effects on mothers and their infants. A previous history of depression appears to be the strongest risk factor for PPD. Previous studies showed that individuals with history of depression accurately recall more negative compared to positive content. The objective of this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…10 Given that previous studies have shown that elevated levels of sCORT and sAA during incidental encoding is associated with better memory for emotional content, 11 and individuals currently depressed recall more negative compared to positive content, 12 our results suggested that clinical remission may be associated with an opposite cognitive processing of negative emotional information. 10 …”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…10 Given that previous studies have shown that elevated levels of sCORT and sAA during incidental encoding is associated with better memory for emotional content, 11 and individuals currently depressed recall more negative compared to positive content, 12 our results suggested that clinical remission may be associated with an opposite cognitive processing of negative emotional information. 10 …”
Section: Introductionmentioning
confidence: 60%
“…Participants returned a week later to complete the incidental recognition memory task. 10 It is important to note that these results were positive in the whole sample. sCORT means for the high-and low-risk groups immediately after the task were 3.63 and 2.97 nmol/L, respectively.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although estrogen plays a crucial role in fertility, psychopathologies such as mood and anxiety disorders involving estrogen dysregulations have been reported (Heldring et al., 2007; McEwen, 1998; Sakaki & Mather, 2012; Wheelan et al., 2018). Interactions with other hormones show that estrogen receptor (ER) activation acts to induce oxytocin receptor expression.…”
Section: Resultsmentioning
confidence: 99%
“…When priming is used to probe memory for semantically encoded materials, people with current MDD/dysthymia favour negative over positive materials, which is the opposite of healthy control participants [17]. In contrast, studies using a recognition memory task demonstrated intact recognition memory for both positive and negative materials [1820] despite impaired valence-independent recall [19] in current MDD or, intriguingly, decreased negative and intact positive recognition memory in pregnant women with rMDD [21]. One study found subtle effects of personal relevance rather than valence or overall recognition memory performance in current MDD [20].…”
Section: Introductionmentioning
confidence: 99%